SURFACE DOSE ESTIMATION BY A KAP METER FOR KILOVOLTAGE X-RAY BEAMS. Issue 2 (19th August 2021) - Araki, F; Umeno, S
Abstract: This study aims to estimate the entrance surface dose (ESD) of a water phantom for kilovoltage x-ray beams using an air kerma area product meter (KAP meter) equipped in an x-ray unit. The KAP meter was calibrated in terms of the ESD determined by a plane-parallel ionization chamber based on a 60 Co absorbed dose-to-water calibration coefficient, N_D, w^^60Co . The ESD measured using the KAP meter was verified by comparing it with that estimated by the air kerma calibration coefficient, NK, for x-ray beam qualities. The ratio of ESDs based on N_D, w^^60Co and NK was 1.003 on average and independent of the beam quality. The ESD by the KAP meter was an agreement within ±1.5% with that measured using the plane-parallel chamber for 10 × 10–30 × 30 cm 2 fields with a source-surface distance of 75–150 cm. It was possible to estimate the ESD directly in a water phantom for x-ray beams without correction factors compared to the existing air kerma calibration, using a KAP meter calibrated based on N_D, w^^60Co .